Pregnancy outcomes of COVID-19 positive pregnant women at the Cantonal Hospital Zenica, Bosnia and Herzegovina - Jasmin Hodžić; Bedrana Muračević; Hana Štimjanin; Rasim Iriškić; Muamera Husika (Medicinski glasnik, 2022)
Aim: To investigate clinical presentation of COVID-19 infection in pregnancy, its course during pregnancy, effects on pregnancy outcomes for both mothers and newborns as well as the potential for vertical transmission. Methods: This retrospective observational study included all identifi ed COVID-19-positive pregnant women admitted to the Cantonal Hospital in Zenica at any stage of pregnancy or labour from 30 April 2020 to April 30 2021. Maternity and newborns were followed until discharge from the hospital. Results: Twenty-four pregnant women were positive for COVID-19. There were 79.2% asymptomatic cases, 12.5% had mild symptoms, while 8.3% had more severe forms of the disease. The main follow-up morbidities were high BMI 33.3%, anaemia 16.7%, thrombocytopenia 12.5%, hypertensive disorders 4.2% and diabetes 4.2%. The rate of premature births was 33.3%, while 8.3% pregnant women had premature rupture of the amniotic sac. Caesarean section was done for 75% women while 25% delivered vaginally. Previous caesarean section (54.2%) was the most common indication for operative completion of labour. Twentythree (92%) live babies were born, of which 8 (33.3%) were admitted to the neonatal intensive care unit. Two (8%) intrauterine foetal deaths were recorded that occurred before admission to our hospital. Two infants (8.7%) had a positive PCR test for COVID-19. Conclusion: COVID-19 viral disease in pregnancy is usually presented as an asymptomatic or mild disease. It is associated with high rates of preterm birth, admission of newborns to the intensive care unit and intrauterine foetal death. Vertical transmission is possible but the newborns were asymptomatic.
Keywords: COVID-19; pregnancy; pregnancy outcome; SARSCoV-2; vertical infection transmission